PENGARUH TINGKAT KEPERCAYAAN DAN KUALITASPELAYANAN TERHADAP KEPUASAAN KONSUMENSICEPET EXPRES KOTA BIMA - Akhmad Ridwan; Muhajirin Muhajirin (Universitas Mahendradatta, 2021)
Satisfying consumer needs is the dream of every company. Apart from beingan important factor for the company's survival, meeting consumer needs canincrease its superiority in competition. Consumers who are satisfied with the level oftrust and service quality are more likely to buy back the product and reuse theservice when the same needs reappear at a later date. This study aims to determinethe effect of the level of trust and service quality on customer satisfaction on the fastexpress in the city of Bima. This study uses a quantitative approach with a surveymethod, while this type of research includes associative research. The population inthis study are consumers who have used the fast express service of the service, thenumber of samples taken in this study were 100 respondents. The sample used in thisstudy was purposive sampling. The research instrument used a questionnaire with aLikert scale. Data analysis used multiple linear regression, correlation test,determination test, partial test analysis with t test and f test (simultaneous). To testthe effect between variables using SPSS (Statistical Service Product Solutions)version 23.00. The results of the study based on the t test (partial) show that the levelof trust has an effect on customer satisfaction, service quality has an effect oncustomer satisfaction, while the level of trust and service quality simultaneouslyaffects customer satisfaction